Penerapan model pembelajaran missouri mathematics project (MMP) untuk meningkatkan keterampilan pemecahan masalah pada peserta didik kelas IV sekolah dasar - Mierza Prizka Camelia; Siti Kamsiyati; Anesa Surya (Universitas Sebelas Maret, 2022)
Increasing the problem solving skills by applying Missouri Mathematics Project model is the purpose of this research. This research is Classroom Action research with two cycles. Students of the 4th SD N Setono No.95 Surakarta on the 2019/2020, the subject all of students at class totaling 33 students. Data collection techniques in the form of interview, observation, test, and documentation. Data analysis are source and technique triangulation, and content validity. Analysis of the data used is the Miles-Huberman interactive analysis model. The initial conditions of problem solving skills of 4th students showed 0%. The cycle I resulting in a percentage is 30,3%. The cycle II producing a percentage is 84,84%. Based on the result of the research, it can be conclude that the problem solving skills on 4 th students of SD N Setono No. 95 Surakarta in the 2019/2020 can be improved through the Missouri Mathematics Project model. This research contributed to be used as a reference and be a development in varied learning activities in mathematics subject.